Tactile Display for Virtual 3D Shape Rendering - Mansutti, Alessandro; Covarrubias Rodriguez, Mario; Bordegoni, Monica; Cugini, Umberto; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book describes a novel system for the simultaneous visual and tactile rendering of product shapes which allows designers to simultaneously touch and see new product shapes during the conceptual phase of product development. This system offers important advantages, including potential cost and time savings, compared with the standard product design process in which digital 3D models and physical prototypes are often repeatedly modified until an optimal design is achieved. The system consists of a tactile display that is able to represent, within a real environment, the shape of a product. Designers can explore the rendered surface by touching curves lying on the product shape, selecting those curves that can be considered style features and evaluating their aesthetic quality. In order to physically represent these selected curves, a flexible surface is modeled by means of servo-actuated modules controlling a physical deforming strip. The tactile display is designed so as to be portable, low cost, modular, and high performing in terms of the types of shape that it can represent.
Introduction -- Related works -- Research context and concept of the system -- Conceptual development of the tactile interface -- Module with indirect actuation system -- Module with direct actuation system -- Discussion and users test -- Augmented Reality visualisation system -- Conclusions and Future Works.
Keywords: Engineering design; User interfaces (Computer systems).; Human-computer interaction; Control engineering; Robotics; Automation; Computer-aided engineering; Engineering Design; User Interfaces and Human Computer Interaction; Control, Robotics, Automation; Computer-Aided Engineering (CAD, CAE) and Design